Oxime-mediated in vitro reactivation kinetic analysis of organophosphates-inhibited human and electric eel acetylcholinesterase - Sahu, Arvind Kumar; Sharma, Rahul; Gupta, Bhanushree; Musilek, Kamil; Kuca, Kamil; Acharya, Jyotiranjan; Ghosh, Kallol K (Toxicology mechanisms and methods, 2016)
Organophosphate (OP)-based pesticides and nerve agents are highly toxic compounds which interrupt the catalytic mechanism of acetylcholinesterase (AChE) by phosphorylating the hydroxyl moiety of serine residue. The inhibited enzyme can be reactivated by the nucleophilic action of oxime reactivators. To analyze the effect of different AChE sources on reactivation efficacy of reactivators, several in vivo studies have carried out using variety of AChE sources like pig, rat and monkey. Investigations on species differences provide a better insight for the development of new reactivators. Hence, present study was mainly targeted on comparative analysis of the reactivation of electric eel and human AChE inhibited by different OP. A series of butene-linked bis-pyridinium mono oximes which vary in functional groups present at the second pyridinium ring have been examined against sarin, VX, tabun and ethyl-paraoxon-poisoned AChE. In case of tabun-inhibited AChEs, tested oximes were better than reference oximes. For VX-poisoned human AChE, reactivator K251 (kr2;1.51 mM (-) (1 )min (-) (1)) showed good reactivation efficacy with standard oximes. Studies stipulated that butene-linked oximes consisting of different functional moieties are good reactivators and found to have better efficacy to reactivate nerve agent-inhibited human AChE in comparison to eel AChE.
Keywords: kinetika; oxime; Adult; erytrocytární membrána; Cholinesterase Inhibitors; oximy; Oximes; Erythrocyte Membrane; nerve agents; reactivation; organophosphate; organofosfáty; Dose-Response Relationship, Drug; Electrophorus; lidé; vztah mezi dávkou a účinkem léčiva; Organophosphates; cholinesterasové inhibitory; acetylcholinesterasa; reaktivátory cholinesterasy; mužské pohlaví; pesticides; časové faktory; dospělí; Animals; Humans; Acetylcholinesterase; Kinetics; Male; Cholinesterase Reactivators; Time Factors; zvířata